The prevalence of kidney failure in diabetic patients with and without anemia: A systematic review and meta-analysis - Monireh Faghir Ganji; Alireza Ansari-Moghaddam; Alireza Amanollahi; Reza Fallahi; Narjes Abdolmohammadi (Elsevier, 2024)
Background: Chronic Kidney Disease (CKD) as a leading cause of death is a major health problem. One of the major contributor of CKD is diabetes. On the other hand, anemia as a common complication of CKD among diabetics increases risk of morbidity and mortality. Then, this meta-analysis identified the prevalence of kidney failure in the diabetic individuals with and without anemia. Methods: We searched electronic databases such as PubMed, MEDLINE, Web of Science, Google Scholar, and Scopus from 2010 to 2023 to find out related reports. Data were extracted by two reviewers independently. The random-effect model used to calculate pooled estimates. Heterogeneity of studies assessed using Q statistic. Data were analyzed using Stata software version 17. Results: This study included a total of 8348 participants with an age range of 45-63 years. The combined prevalence of kidney disease in anemic patients was 28.29 % [31.28 % in diabetic anemic patients compared to 15.08 % in those without anemia (P for heterogeneity <0.001)]. The pooled Odds Ratio between kidney disease and anemia was 5.12 (95 % CI: 3.84-7.54). There was no evidence of publication bias in the study. Conclusions: In conclusion, the prevalence of kidney disease was found to be significantly higher in anemic patients, particularly in those with diabetes. Therefore, anemia seems to be a significant risk factor for kidney disease mainly amongst diabetics. Consequently, there should be comprehensive programs to address anemia among population in principally in diabetic patients.